Critical Analysis of Mystical Prayer Studies in the Intellectual Doctrine of Shaykh Ahmad al-Alāvī - Mojtaba Etemadinia (پژوهش در آموزش معارف و تربیت اسلامی)
The purpose of the present study is to review the exegetical views of Shaykh Ahmad al-Alāvī(a noble mystic from North Africa in the 20th century) about the subject of Namāz (Prayer). In this regard, various meanings and applications of the term "Salāt" as well as the enigmatic and innate meanings of its constituents and requirements as a religious hypothesis were studied. The method of study was descriptive analysis and the results showed that based on Alāvī's mystical prayer studies, Namāz is a symbolic representation of stages of the mystical journey and reaching levels of the mystics. All classifications, conditions, duties, traditions, and Makrūhāt (reprehensible legal values in Islamic law) in the concept of Namāz involve enigmatic and innate meanings in terms of the mystical journey. In this regard, the jurisprudential rules and inferences about religious duties all originate from a Takwīnī (creational) source. The exegetical approach of Alāvī to the explanation and interpretation of enigmatic and innate meanings of jurisprudential rules, like many other similar instances, is faced with some challenges such as formality and ambiguity in decoding jurisprudential rules, bringing paradoxical and incompatible justifications, and above all, belief in a Takwīnī (creational) source for the paradoxical and contradictory jurisprudential rules.